2001
DOI: 10.1097/00002480-200109000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Safety Observations in Phase I Clinical Evaluation of the Excorp Medical Bioartificial Liver Support System after the First Four Patients

Abstract: A Phase I clinical safety evaluation of the Excorp Medical, Inc, Bioartificial Liver Support System (BLSS) is in progress. Inclusion criteria are patients with acute liver failure of any etiology, presenting with encephalopathy deteriorating beyond Parson's Grade 2. The BLSS consists of a blood pump, heat exchanger to control blood temperature, oxygenator to control oxygenation and pH, bioreactor, and associated pressure and flow alarm systems. Patient liver support is provided by 70-100 g of porcine liver cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 10 publications
0
48
0
1
Order By: Relevance
“…There was another study that reported four cases with ALF treated with BLSS. 112 All the four patients could tolerate the treatment well, and the average levels of ammonia and total bilirubin levels were lower than before treatment by 33% and 6%. During the hemoperfusion, except for the hypoglycemia of four patients at the start phase, and the low blood pressure of one patient that was corrected promptly, there were no other serious complications.…”
Section: Excorp Medical Bioartificial Liver Support Systemmentioning
confidence: 79%
See 1 more Smart Citation
“…There was another study that reported four cases with ALF treated with BLSS. 112 All the four patients could tolerate the treatment well, and the average levels of ammonia and total bilirubin levels were lower than before treatment by 33% and 6%. During the hemoperfusion, except for the hypoglycemia of four patients at the start phase, and the low blood pressure of one patient that was corrected promptly, there were no other serious complications.…”
Section: Excorp Medical Bioartificial Liver Support Systemmentioning
confidence: 79%
“…Cells are mixed with collagen to infuse into hollow fiber bioreactor so that collagen gel matrix is formed in the extracapillary region for cell anchorage. 112 Detry et al 113 developed HepatAssist 2000, in which collagen-coated dextran microcarriers are used for porcine hepatocytes attached and are housed in the extracapillary compartment in the bioreactor. The Academic Medical Center ͑AMC͒ EBAL system loads a nonwoven hydrophilic polyester matrix in the extrafiber region in the bioreactor for hepatocytes' attachment while the inner-lumen of hollow fibers are used for oxygen supply.…”
Section: A Hollow Fiber Cartridgementioning
confidence: 99%
“…The cells mixed with collagen are infused into the extracapillary space of fibers. Following the 12-h treatment, PERV transmission from the animal cells to patients was not observed (Mazariegos et al 2001;Kuddus et al 2002). Survival outcome has not been reported for this system.…”
Section: Liver Support Systems In Preclinical and Clinical Testmentioning
confidence: 84%
“…Различия в конструкции таких биореакторов заключаются в методах прикрепления гепатоцитов. Так, в аппарате ELAD (Extracorporeal liver assist device) гепатоциты человека С3А располагают в экстралюминальном пространстве волокон [36], в аппарате BLSS (Bioartificial liver support system) используют суспензию гепатоцитов свиней в коллагеновом геле [84], в устройстве для аппарата HepatAssist 2000 [85] для иммобилизации гепатоцитов свиней использовали декстрановые микрочастицы, а в апаратах фирмы Academic Medical Center -гидрофильный матрикс на основе полиэфиров [86]. В 2001 году была предложена конструкция MELS (Modular extracorporeal liver support) с более сложным катриджем, состоящим из трёх компартментов полых волокон, выполняющих функции перемещения плазмы, обеспечения гепатоцитов кислородом и питательными веществами [87].…”
Section: биореакторы на основе катриджей из полых волоконunclassified